2016
DOI: 10.1002/2016ja022455
|View full text |Cite
|
Sign up to set email alerts
|

The 11 year solar cycle signature on wave‐driven dynamics in WACCM

Abstract: This study describes the influence of the 11 year solar cycle on gravity waves and the wave‐driven circulation, using an ensemble of six simulations of the period from 1955 to 2005 along with fixed solar maximum and minimum simulations of the Whole Atmospheric Community Climate Model (WACCM). Solar cycle signals are estimated by calculating the difference between solar maximum and minimum conditions. Simulations under both time‐varying and fixed solar inputs show statistically significant responses in temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
21
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 31 publications
7
21
2
Order By: Relevance
“…A recent addition is that above 95 km, the climatological trueU¯ in Austral winter is westerly (Qian et al, ; Smith et al, ). Similar to Cullens et al () and Gan et al (), our results in Figure c show that during solar maximum, trueU¯ below 80 km is enhanced. This drives a poleward and downward residual circulation anomaly between 50 and 80 km over the midlatitudes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A recent addition is that above 95 km, the climatological trueU¯ in Austral winter is westerly (Qian et al, ; Smith et al, ). Similar to Cullens et al () and Gan et al (), our results in Figure c show that during solar maximum, trueU¯ below 80 km is enhanced. This drives a poleward and downward residual circulation anomaly between 50 and 80 km over the midlatitudes.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, there is an easterly anomaly in trueU¯ below 80 km over 60°S to 50°S shown in Figure c. This is consistent with Kodera and Kuroda (), Cullens et al (), and Gan et al () where they additionally showed that this easterly trueU¯ anomaly is due to anomalies in planetary wave propagation. This easterly anomaly should weaken the mesospheric easterly winter jet, which should allow more westerly gravity waves to propagate.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We note that the alternate structure is initially located around ~45°S and 65 km in June and tends to go poleward and downward in July and August. This midlatitude alternate structure in temperature as the response to the SC has been previously reported by the ground‐based observation and modeling studies [ Keckhut et al ., ; Hampson et al ., ; Li et al ., ; Cullens et al ., ]. Figure displays the corresponding zonal wind responses during the same time span.…”
Section: Resultsmentioning
confidence: 99%
“…Kodera and Kuroda [] reported similar westerly wind anomalies, which move downward and poleward as the response of the SC in the NH winter. The similar manner in the zonal wind was also confirmed by WACCM circulation model [ Cullens et al ., ]. They argued that anomalous planetary wave activities are the key cause to the zonal wind anomalies under the solar maximum condition.…”
Section: Resultsmentioning
confidence: 99%